IN-SITU POLYMER BLENDS VIA CHAIN TRANSFER LIVING POLYMERIZATION (CTLP) - YOON, HS; KIM, KU; LEE, J; LEE, Y; HWANG, SS; PARK, TS; CHO, J; KIM, J; AHN, BI; CHAR, K; QUIRK, RP (WILEY-V C H VERLAG GMBH, 1995)
In-situ polymer blends of polystyrene (PS)/poly(methyl methacrylate) (PMMA) with controlled and variable different compositions and molecular weights were found to be successfully synthesized by ''chain transfer living polymerization (CTLP)'' methodology by a combination of size-exclusion chromatographic analysis, differential scanning calorimetry (DSC), UV/Vis and H-1 NMR spectroscopy, and optical microscopic analysis. The PMMAs prepared in tetrahydrofuran (THF) in the presence of polystyrene exhibit highly syndiotactic stereoregularity (over 70 mol-%) and a glass transition temperature over 120 degrees C. A dispersed morphology was found even for blends with over 31 vol.-% of the weight fraction of one component due to the discrepancy in the molecular weights of two components in the PS/PMMA blends. A ternary polymer blend system having PS/PMMA/PS -block- PMMA can be generated by control of the concentration of fluorene as the chain transfer agent in the CTLP.
Keywords: POLY(METHYL METHACRYLATE) BLENDS; ETHYLENE-OXIDE; COPOLYMERS; MONOMERS